2021
DOI: 10.3390/ijms222212577
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Visual Detection of Heterodera schachtii Using Recombinase Polymerase Amplification Combined with Cas12a-Mediated Technology

Abstract: Heterodera schachtii is a well-known cyst nematode that causes serious economic losses in sugar beet production every year. Rapid and visual detection of H. schachtii is essential for more effective prevention and control. In this study, a species-specific recombinase polymerase amplification (RPA) primer was designed from a specific H. schachtii sequence-characterized amplified region (SCAR) marker. A band was obtained in reactions with DNA from H. schachtii, but absent from nontarget cyst nematodes. The RPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The integration of the CRISPR-Cas12a and nucleic acid amplification techniques has been proved by several works. 22,60,63–65 These results demonstrated that our nanopore sensor using a DNA tetrahedron as a signal transducer based on the CRISPR-Cas12a conversion mechanism could detect targets specifically, which we believe could become a promising alternative to biomolecular detection.…”
Section: Resultsmentioning
confidence: 74%
“…The integration of the CRISPR-Cas12a and nucleic acid amplification techniques has been proved by several works. 22,60,63–65 These results demonstrated that our nanopore sensor using a DNA tetrahedron as a signal transducer based on the CRISPR-Cas12a conversion mechanism could detect targets specifically, which we believe could become a promising alternative to biomolecular detection.…”
Section: Resultsmentioning
confidence: 74%
“… 33 A CRISPR-Cas12 system may be used to detect the genome of these organisms as well, as already reported in some pioneer studies. 34 36 Furthermore, because of the exquisite sequence recognition ability of these systems, the genetic diversity of a given pathogen might be detected (at least some variants). Continuous monitoring of different pathogens in the field should help to implement better control strategies incorporating ecological concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, it is critical and necessary to develop a rapid and field-friendly diagnosis tool for better prevention and control this disease. Yao et al [74] combined RPA with CRISPR-Cas12a technology to successfully detect plant samples infected with H. schachtii within 1 hour by fluorescence. The sensitivity of the system developed was greater than electrophoresis and was similar to that of an RPA/lateral flow dipstick procedure reported in the same study.…”
Section: Malariamentioning
confidence: 99%
“…Supported by the ever expanding numbers of pre-clinical and clinical studies which have shown the utility of CRISPR-Cas12/13-based diagnosis for viral diseases (especially SARS-CoV-2) and cancer, the CRISPR-mediated approach has been extended for the ultrasensitive detection of the single-celled parasites including Cryptosporidium parvum, [34,35] Enterocytozoon hepatopenaei, [36] malaria, [33,73] and a plant-parasitic nematode -Heterodera schachtii. [74]…”
Section: Deployment Of the Crispr-cas System For The Diagnosis Of Par...mentioning
confidence: 99%